NaOH wheat silage and alfalfa haylage for growing steers and heifers - Bolsen, K.; Ilg, H.; Nuwanyakpa, M.; Hoover, J. (Kansas State University. Agricultural Experiment Station, 2011)
Wheat silage, with and without sodium hydroxide (NaOH), was fed, with or without alfalfa haylage, in an 80-day growing trial. Calves fed NaOH-silage consumed 18% more feed and gained 16% faster than those fed control silage, but feed efficiencies were similar. When 50% of the wheat silage was replaced with alfalfa haylage (DM basis), gains decreased 3.1 and 3.7%, feed intake increased 12.3 and 9.7%, and feed efficiency decreased 23.7 and 14.4% for calves fed control and NaOH silages, respectively. NaOH increased ensiling temperatures by 9 to 12° C during the first 6 weeks. Dry matter recovery from the concrete stave silos was similar for both silages (82.1% for control and 83.9% for NaOH); recoveries from buried bags were 92.3 and 89.5%. NaOH wheat silage was more stable in air than was either control wheat silage or alfalfa haylage.
Keywords: Beef; Sodium hydroxide; Wheat silage; Alfalfa haylage; Steers; Heifers